2006
DOI: 10.1200/jco.2006.07.1100
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Adoptive T-Cell Therapy Using Antigen-Specific CD8+ T Cells for the Treatment of Patients With Metastatic Melanoma

Abstract: Our data indicate that the adoptive transfer of antigen-specific T cells in melanoma patients can induce clinical tumor-specific immune responses without major adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(209 citation statements)
references
References 25 publications
6
195
0
8
Order By: Relevance
“…Although T cell clones can be expanded over two weeks to achieve numbers >10 10 , there are additional weeks needed to generate the clones first and the cloning process is laborious (Yee et al, 2002). Mackensen and his colleagues (Mackensen et al, 2006) established a protocol to generate M27L-specific T cells by stimulating CD8+ lymphocytes (selected by beads) with dendritic cells weekly for 4 weeks. Of 11 patients treated, there were a total of 52 infusions, with an average of 2x10 8 M27L-specific T cells in each infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although T cell clones can be expanded over two weeks to achieve numbers >10 10 , there are additional weeks needed to generate the clones first and the cloning process is laborious (Yee et al, 2002). Mackensen and his colleagues (Mackensen et al, 2006) established a protocol to generate M27L-specific T cells by stimulating CD8+ lymphocytes (selected by beads) with dendritic cells weekly for 4 weeks. Of 11 patients treated, there were a total of 52 infusions, with an average of 2x10 8 M27L-specific T cells in each infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immunogenicity of a number of TAA has been documented in clinical trials, their therapeutic potential has not been clearly assessed, with the exception of the Melan-A/MART-1 antigen. Indeed, the therapeutic usefulness of the Melan-A antigen in melanoma is supported by the analysis of several active [2,3] and passive [4][5][6][7][8][9] immunotherapy protocols targeting this antigen.…”
Section: Introductionmentioning
confidence: 99%
“…However, considerable research has shown that the persistence of transferred T cells in vivo is both central to therapeutic success and elusive to current technology (6,7). The efficacy of adoptive immunotherapy in humans is often limited by the failure of transferred T cells to survive in the host (8,9).…”
mentioning
confidence: 99%